Emerging Technologies to Enable Sustainable Controlled Environment Agriculture in the Extreme Environments of Middle East-North Africa Coastal Regions - Lefers, Ryan M.; Tester, Mark; Lauersen, Kyle J. (Frontiers in Plant Science, 2020)
Despite global shifts in attitudes towards sustainability and increasing awareness of human impact on the environment, projected population growth and climate change require technological adaptations to ensure food and resource security at a global scale. Although desert areas have long been proposed as ideal sites for solar electricity generation, only recently have efforts shifted towards development of specialized and regionally focused agriculture in these extreme environments. In coastal regions of the Middle East and North Africa (MENA), the most abundant resources are consistent intense sunlight and saline sea water. MENA coastal regions hold incredible untapped potential for future agriculture driven by the combination of key emerging technologies in future greenhouse concepts: transparent infrared collecting solar panels and low energy salt water cooling. These technologies can be combined to create greenhouses that drive regionally relevant agriculture in this extreme environment, especially when the target crops are salt-tolerant plants and algal biomass. Future controlled environmental agriculture concepts will not compete for municipal fresh water and can be readily integrated into local human/livestock/fisheries food chains. With strategic technological implementation, marginal lands in these environments could participate in production of biomass, sustainable energy generation, and the circular carbon economy. The goal of this perspective is to reframe the idea of these environments as extreme, to having incredible untapped development potential.